Agency Theory Applied to the Italian Revenue Agency: Accountability Policies as Bonding Costs - Castellini, Monia; Riso, Vincenzo (European Scientific Journal, ESJ, 2016)
This paper aims at studying the consequences of the Agency Theory application at the case of the Italian Revenue Agency (afterwards IRA). The major countries in the world entrust the tax administration to the Agencies that make use of various strategies to manage tax revenue and to contrast tax avoidance. In the last years the Organisation for Economic Co-operation and Development (afterwards OECD) has invited many States to increase the tax compliance between Public Tax Administration and Taxpayers and to improve the relationship with these. There are more scientific contributions about the themes like the Agency Theory, the Stakeholder’s Theory and other more on Governance and Accountability policies: many of these will be discussed in this work. In the light of these observations the research question is: given that IRA plays a central role in the tax administration, what happen if we apply the Agency Theory on this? What are the Agency costs in this case? To answer to these question we have studied the Law provisions in the Italian tax field and the “way to do” of the IRA. So, this work not is only a theoretical analysis of the scientific literature but it move to analyse the implications of these on the real case. The conclusions achieved in this paper are based on the analysis of the Italian case that only partially brings a solution to this question. However it represent the first point for us to beginning a future comparison between the evidences in the international context.